Perkembangan Sejarah Pemikiran Ekonomi Islam Periode 1960-1980 - S, Zul Ikram; Sirajuddin; Parakkasi, Idris (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This paper aims to investigate developments and changes in Islamic economic thought during the period 1960-1980. This period is very important in the history of Islamic economic thought because it experienced many social, political, and economic changes in the Muslim world. This study uses historical analysis methods to trace the evolution of Islamic economic thought at that time. This paper identifies several key figures and schools of thought that played an important role in developing Islamic economic thought in that period. Some of the figures studied include Sayyid Abul A'la Maududi, Sayyid Qutb, and Muhammad Baqir as-Sadr, who represent diverse views in Islamic economic thought. The results of this study indicate that the period 1960-1980 was an important period in the development of Islamic economic thought. During this period, attempts were made to combine the principles of Islamic economics with contemporary economic practices. Several schools of thought propose alternative economic models based on Islamic principles, such as an economic system based on social justice, sustainable economic development, and economic empowerment of Muslims. Keywords: Islamic Economic Thinking, History